Using Q-methodology in environmental sustainability research: A bibliometric analysis and systematic review - Sneegas, Gretchen (2021)
Q-methodology is a mixed qualitative-quantitative method used to measure social perspectives on issues relating to sustainability and environmental governance in a systematic, replicable manner. Although it has grown in prominence and use over the past two decades, to date there has not been a comprehensive review of the environmental sustainability Q-methodology literature. Using bibliometric analysis and systematic review, this paper examines the rapid growth in published Q-methodology research on sustainable natural resource management and environmental governance. We analysed and iteratively coded 277 empirical Q-studies published between 2000-2018 to establish research trends, shared gaps, and best practices among environmental social science Q-researchers. We also conducted co-authorship and co-citation analyses to identify research clusters using Q-methodology. We find that, while Q-methodology uses a relatively standardized protocol, considerable heterogeneity persists across such domains as study design, p-set identification, concourse and Q-set development, analysis and interpretation. Further, we identify major reporting gaps among Q-methodology publications where researchers do not fully describe or justify subjective decision-making throughout the research phases. The paper ends with recommendations for improving research reporting and increasing the circulation and uptake of up-to-date Q-methodology practices and innovations.